TOPSIS Decision on Approximate Pareto Fronts by Using Evolutionary Algorithms: Application to an Engineering Design Problem - Méndez, Máximo (2020)
Fil: Méndez, Máximo. Universidad de Las Palmas de Gran Canaria (ULPGC). Instituto Universitario SIANI. Las Palmas de G.C., Spain